1998
DOI: 10.1002/(sici)1097-0185(199801)250:1<117::aid-ar12>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Potential use of embalmed cadavers to study mast cell presence

Abstract: Background: Embalmed cadavers in medical classes represent a potential source for collecting human tissues without the inherent problems of obtaining fresh or surgical specimens. Although the manner of fixation and vagaries of embalming techniques eliminate many such tissues for histological assessment, other techniques can be applied successfully to embalmed tissues. Pertinent to the present study, mast cells contain granules that are preserved under good fixation in formalde-hyde, a main ingredient in embalm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Embalmed cadaveric material has generally been avoided for histological purposes, as the fixation achieved through the process of whole body embalming has been considered inadequate for histological specimens (MacBride 1998). The quality of embalmed tissue is affected by the time that elapses between death and the embalming process, the patency of the peripheral blood vessels, and the age and cause of death of the individual.…”
Section: Introductionmentioning
confidence: 99%
“…Embalmed cadaveric material has generally been avoided for histological purposes, as the fixation achieved through the process of whole body embalming has been considered inadequate for histological specimens (MacBride 1998). The quality of embalmed tissue is affected by the time that elapses between death and the embalming process, the patency of the peripheral blood vessels, and the age and cause of death of the individual.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, the study was carried out on muscle tissue from cadavers treated with a Formaldehyde based embalming fluid as per Glasgow University embalming protocols. This may result in the tissues becoming hard, rigid and often difficult to dissect [ 26 ]. MacBride [ 27 ] also suggested that studies using embalmed cadavers were often avoided because the fixation process was poor, making tissues less suitable for histological examination.…”
Section: Discussionmentioning
confidence: 99%
“…Electron-microscopic studies have demonstrated that avidin binds highly preferentially to individual mast cell granules rather than to other cellular structures (Bussolati and Gugliotta 1983; Jones et al 1987; Tharp et al 1985), and rodent or human mast cells are known to be readily stained with avidin conjugated to horseradish peroxidase (Bussolati and Gugliotta 1983; Kasper and Tharp 1987) or to certain fluorochrome dyes (Tharp et al 1985; Markey et al 1989; MacBride 1998). Based on the results, we decided to use an adivin gold (AvG) complex as a cationic probe for detection of anionic sites in mast cell granules and other structures.…”
Section: Introductionmentioning
confidence: 99%